Interactions of hydrogen sulfide with myeloperoxidase - Pálinkás, Zoltán (Br J Pharmacol, 2015)
BACKGROUND AND PURPOSE: The actions of hydrogen sulfide in human physiology have been extensively studied and, although it is an essential mediator of many biological functions, the underlying molecular mechanisms of its actions are ill-defined. To elucidate the roles of sulfide in inflammation, we have investigated its interactions with human myeloperoxidase (MPO), a major contributor to inflammatory oxidative stress. EXPERIMENTAL APPROACH: The interactions of sulfide and MPO were investigated using electron paramagnetic resonance, electronic circular dichroism, UV-vis and stopped-flow spectroscopies. KEY RESULTS: We found favourable reactions between sulfide and the native-ferric enzyme as well as the MPO redox intermediates, ferrous MPO, compound I and compound II. Sulfide was a potent reversible inhibitor of MPO enzymic activity with an IC(50) of 1 µM. In addition, the measured second-order rate constants for the reactions of sulfide with compound I [k = (1.1 ± 0.06) × 10(6) M(−1) s(−1)] and compound II [k = (2.0 ± 0.03) × 10(5) M(−1) s(−1)] suggest that sulfide is a potential substrate for MPO in vivo. CONCLUSION AND IMPLICATIONS: Endogenous levels of sulfide are likely to inhibit the activity of circulating and endothelium-bound MPO. The fully reversible inhibition suggests a mediatory role of sulfide on the oxidant-producing function of the enzyme. Furthermore, the efficient HOCl oxidation of sulfide to give polysulfides (recently recognized as important components of sulfide biology) together with MPO-catalysed sulfide oxidation and the lack of interaction between MPO and sulfide oxidation products, predict a modulatory role of MPO in sulfide signalling. LINKED ARTICLES: This article is part of a themed section on Pharmacology of the Gasotransmitters. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2015.172.issue-6